2013
DOI: 10.1108/jfra-04-2012-0018
|View full text |Cite
|
Sign up to set email alerts
|

The impact of audit committee existence and external audit on earnings management

Abstract: Purpose – This study aims to examine the combined effect of audit committee existence and external audit on earnings management. Design/methodology/approach – The paper uses ordinary least squares regression model to examine the effect of audit committee existence, external audit and the interaction between these two monitoring mechanisms on earnings management for a sample of 33 non-financial listed Portuguese firms-year from 2003 to 2009. Findings – In contrast to results of most previous studies, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
0
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 86 publications
11
56
0
15
Order By: Relevance
“…Furthermore, this research finding showed that large firms have higher levels of EM, indicating that larger firms are better able to manage earnings and camouflage actual performance (Alves, 2013;Chen et al, 2007). This study also showed significantly positive association between EM and leverage.…”
Section: Multivariate Analysis and Results Interpretationsupporting
confidence: 57%
See 4 more Smart Citations
“…Furthermore, this research finding showed that large firms have higher levels of EM, indicating that larger firms are better able to manage earnings and camouflage actual performance (Alves, 2013;Chen et al, 2007). This study also showed significantly positive association between EM and leverage.…”
Section: Multivariate Analysis and Results Interpretationsupporting
confidence: 57%
“…However, greatly indebted companies might be less capable to exercise EM as they are monitored by lender assessment. Prior authors found a positive association between leverage and EM (Alves, 2013;Gerayli et al, 2011;Sweeney, 1994), while others reported a negative relationship (Park and Shin, 2004;Peasnell et al, 2000). For this study, leverage (LEV) is the total debt divided by the total assets (at the start of the year).…”
Section: Measurement Of the Control Variablesmentioning
confidence: 88%
See 3 more Smart Citations